2015
DOI: 10.1111/1471-0528.13345
|View full text |Cite
|
Sign up to set email alerts
|

Is the probability of prenatal diagnosis or termination of pregnancy different for fetuses with congenital anomalies conceived following assisted reproductive techniques? A population‐based evaluation of fetuses with congenital heart defects

Abstract: Objective To compare the probability of prenatal diagnosis (PND) and termination of pregnancy for fetal anomaly (TOPFA) between fetuses conceived by assisted reproductive techniques (ART) and spontaneously-conceived fetuses with congenital heart defects (CHD).Design Population-based observational study.Setting Paris and surrounding suburbs.Population Fetuses with CHD in the Paris registry of congenital malformations and cohort of children with CHD (Epicard).Methods Comparison of ART-conceived and spontaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Following infertility and an ART pregnancy, the inclination to terminate a pregnancy could be assumed to be lower if detecting a birth defect, which could influence the numbers and the analyses when comparing birth defects in ART and spontaneously conceived children. However, this has not been shown in studies from Finland and France, indicating similar rates on termination of pregnancies in ART and SC pregnancies (Pelkonen et al, 2014, Tararbit et al, 2015.…”
Section: Discussionmentioning
confidence: 78%
“…Following infertility and an ART pregnancy, the inclination to terminate a pregnancy could be assumed to be lower if detecting a birth defect, which could influence the numbers and the analyses when comparing birth defects in ART and spontaneously conceived children. However, this has not been shown in studies from Finland and France, indicating similar rates on termination of pregnancies in ART and SC pregnancies (Pelkonen et al, 2014, Tararbit et al, 2015.…”
Section: Discussionmentioning
confidence: 78%
“…This was supported by a recent French study on congenital heart malformation after ART. They found that malformation data on live‐born children are most likely adequate when assessing the risk of malformations, as they did not find a difference in the rate of pregnancy terminations between ART and SC after identification of severe congenital heart malformations . A potential reporting bias for ART children seems unlikely, since only major malformations were included in this study and would therefore be expected to be detected regardless of mode of conception.…”
Section: Discussionmentioning
confidence: 92%
“…has not received much attention in the literature. A single study on congenital heart defects in France showed no difference in either prenatal diagnosis or the termination of pregnancies between ART and non-ART births (Tararbit et al 2015).…”
Section: Discussionmentioning
confidence: 97%